Improving Students Activity and Mathematic Learning Outcomes by Using Student Facilitator and Explaining Learning Method - Suyviroh Suyviroh; Abd Rahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
The purpose of the research to describe the student activity in using of  student facilitator and explaining method. To describe the students learning outcomes in using of  student facilitator and explaining method. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII B at SMP Satya Dharma – Balung With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is improving students activity and student learning outcomes.Keywords: student facilitator and explaining, students’ activity, and students learning outcomes